Sopesando consideraciones en conflicto: derecho civil y common law frente al problema del vínculo entre las partes en acciones de enriquecimiento injustificado - Letelier Cibié, Pablo (2021)
This article seeks to demonstrate that considering the French approach to the general action in unjustified enrichment may help English law to deal with the difficulties raised by indirect enrichment cases. To do so, it introduces the problem of the link between the parties in English law and compares the German and French approaches to this problem. It is suggested that the cases where the general action in unjustified enrichment has been recognized by French case law are useful to identify a set of considerations that might allow deciding indirect enrichment cases without relying on abstract notions intended to be applied in every possible scenario.